Two Naomis - Rhuday-Perkovich, Olugbemisola; Vernick, Audrey (Balzer + Bray, 2018)
Naomi Marie and Naomi Edith are sure that other than their names, they have nothing in common. And when one's father begins dating the other's mother the girls are forced to find common ground they never cared to share. Now the girls who never cared to be friends could find themselves being something more--they might just become step-sisters.